Answer:
9) y=(-6-3x)/2 10) y=(2x+15)/3 11) y=8+4x
12) y=1/2x+6 13) y= (8-3x)/-4 14) y= (10-6x)/-2
Explanation:
The methods I used are known as float and ping, and escalator:
9) We can float the 3x to the other side to make
2y=-6-3x
We now escalate the 2 down to make:
y=
![(-6-3x)/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/5wqnioib8imckxxqoyggy7cmh7vnm52057.png)
10) We simply escalate the 3 down to give:
y=
![(2x+15)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/6c5sadc7yl4lfpt11unllcttcc18vz676i.png)
11) We simply float the -4x to the other side:
y=8+4x
12) For this question, it will be better to expand the bracket first:
y-8=-1/2x-2
Now we float the -8 to the other side to give:
y=-1/2x-2+8
Which can be simplified to give:
y=1/2x+6
13) We simply float the 3x to the other side to give:
-4y=8-3x
Now we escalate the -4 down to give:
y=
14) We float the 6x to the other side to give:
-2y=10-6x
Now we escalate the -2 down to give:
y=
![(10-6x)/(-2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/trtes4o2ssgt2mz34f63vvuwpy5a4l2kv5.png)